ARE POLICY DECISIONS ON SURGICAL PROCEDURES INFORMED BY ROBUST ECONOMIC EVIDENCE? A SYSTEMATIC REVIEW. (13th November 2014) - Ara, Roberta; Basarir, Hasan; Keetharuth, Anju D.; Barbieri, Marco; Weatherly, Helen L.A.; Sculpher, Mark J.S.; Ahmed, Hashim; Brown, Steven
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The aim of this study was to examine the empirical and methodological cost-effectiveness evidence of surgical interventions for breast, colorectal, or prostate cancer. Methods: A systematic search of seven databases including MEDLINE, EMBASE, and NHSEED, research registers, the NICE Web site and conference proceedings was conducted in April 2012. Study quality was assessed in terms of meeting essential, preferred and UK NICE specific requirements for economic evaluations. Results: The seventeen (breast = 3, colorectal = 7, prostate = 7) included studies covered a broad range of settings (nine European; eight non-European) and six were published over 10 years ago. The populations, interventions and comparators were generally well defined. Very few studies were informed by literature reviews and few used synthesized clinical evidence. Although the interventions had potential differential effects on recurrence and mortality rates, some studies used relatively short time horizons. Univariate sensitivity analyses were reported in all studies but less than a third characterized all uncertainty with a probabilistic sensitivity analysis. Although a third of studies incorporated patients' health-related quality of life data, only four studies used social tariff values. Conclusions: There is a dearth of recent robust evidence describing the cost-effectiveness of surgical interventions in the management of breast, colorectal and prostate cancers. Many of the recent publications did not satisfy essential methodological requirements such as using clinical evidence informed by a systematic review and synthesis. Given the ratio of potential benefit and harms associated with cancer surgery and the volume of resources consumed by these, there is an urgent need to increase economic evaluations of these technologies.